An Analysis of the Effectiveness of the SI-PAL Application in Hospital Quota Management within the Medical Professional Study Program Using the PIECES Method - Edy Hidayat Arsan; Aries Muslim; Amri Sinuraya (Newinera Publisher, 2026)
This study aims to analyze the effectiveness of the SI-PAL Application in hospital quota management in the Medical Profession Study Program, with a focus on optimizing coordination between the Study Program and Komkordik and equalizing the distribution of student clinical rotations. The research method used a quantitative approach with an evaluative model based on the PIECES Framework, which includes the dimensions of Performance, Information, Economy, Control, Efficiency, and Service. The relationship between variables was tested using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method, involving a sample of 202 respondents consisting of program directors, administrators, and students. The analysis results show that the SI-PAL application has a significant effect on the effectiveness of quota management, with a path coefficient value of 0.982 and a coefficient of determination (R^2) of 0.964. This finding indicates that SI-PAL is capable of improving response speed, data exchange reliability, and proportionality of rotation distribution, particularly through automatic plotting mechanisms and concurrency techniques. Evaluation across the six PIECES dimensions also demonstrated the system's superior performance, particularly in terms of information quality, operational efficiency, and user satisfaction.Overall, this study confirms that SI-PAL is an effective digital instrument in supporting clinical rotation management and improving the quality of institutional coordination. However, approximately 3.6% of the variability in quota management performance is influenced by external factors such as network stability, user readiness, and resistance to digital change, thus requiring mitigative strategies to improve overall performance.